Investigation of electronic and thermal properties of CoCrFe and CoCrFeNi high entropy alloys via extended tight-binding DFT computational method - Celik, Fatih Ahmet; Kazanç, Sefa (My University, 2023)
In this study, CoCrFe and CoCrFeNi transition high entropy alloys (HEAs) are modelled by extended tight-binding density functional theory (DFT) method. Also, the geometric optimizations, band structures, density of states (DOS), thermodynamic properties and phonon dispersion curves of alloys are investigated to give a detailed information. The results show that the covalent d–d bonding between Fe-Cr is occurred because of strong metallic Cr–Fe interactions. The entropy (S) value increases gradually with the addition of Ni element to the CoCrFe alloy. The heat capacity (Cv) increases due to the harmonic effect of the phonons in the range of 0-400 K and then, close to the classic limit at high temperatures with 0.82 J/mol.K and 0.94 J/mol.K for the CoCrFe and the CoCrFeNi. The alloy systems exhibit metallic properties because the DOS of the metals have a nonzero value at the Fermi energy level. Also, the addition of element Ni to the CoCrFe alloy system causes a decrease in phonon frequencies.
Keywords: DFT method; Simulation and modelling; high entropy alloys; metals and alloys